Acceptability of Telelactation Services for Breastfeeding Support Among Black Parents: Semistructured Interview Study - Khadesia Howell; Gabriela Alvarado; Molly Waymouth; Jill Demirci; Rhianna Rogers; Kristin Ray; Lori Uscher-Pines (JMIR Publications, 2023)
BackgroundWhile breastfeeding rates have increased in the United States in recent years, racial and ethnic disparities persist. Telelactation may help reduce disparities by increasing access to lactation consultants, but there is limited research on acceptability among minoritized individuals. ObjectiveWe aimed to explore experiences with telelactation among Black parents and identify strategies to make services more culturally appropriate. MethodsWe selected 20 Black parents who were given access to telelactation services from an ongoing National Institutes of Health-funded randomized controlled trial (the Tele-MILC trial) to participate in semistructured interviews. Interviews addressed birth experiences, use and opinions about telelactation, comparison of telelactation to in-person lactation support, and recommendations to improve telelactation services. The thematic analysis was informed by a previously reported theoretical framework of acceptability and RAND Corporation's equity-centered model. ResultsUsers appreciated the convenience of telelactation and reported that lactation consultants were knowledgeable and helpful. Participants wanted more options to engage with lactation consultants outside of video visits (eg, SMS text messaging and asynchronous resources). Users who had a lactation consultant of color mentioned that racial concordance improved the experience; however, few felt that racial concordance was needed for high-quality telelactation support. ConclusionsWhile Black parents in our sample found telelactation services to be acceptable, telelactation could not, in isolation, address the myriad barriers to long-duration breastfeeding. Several changes could be made to telelactation services to increase their use by minoritized populations.